Pediatric physical therapy approach in neurogenic bladder (Research, Society and Development, 2022)
This article aims to investigate through the literature how pediatric physiotherapy can help in the treatment of neurogenic bladder, as well as the best physiotherapeutic treatment for patients affected by this syndrome and how physiotherapy can help in the quality of life of neurogenic bladder patients. Therefore, it is a Study of the Integrative Literature Review type. The following databases were used to survey the articles: Latin American and Caribbean Literature on Health Sciences (LILACS), Medical Literature Analysis and Retrieval System on-line (Medline) and Scientific Electronic Library Online (SCIELO). The following descriptors and their combinations in Portuguese, Spanish and English were used to search for articles: “Physiotherapy”, “Urinary Incontinence”, “Neurogenic Bladder”. At first, the search for the descriptors was given individually, later using the crossing from the Boolean operator “and”. The analyzed studies showed that physiotherapeutic resources such as urotherapy, behavioral therapy, transcutaneous parasacral and posterior tibial electrostimulation, can be used in the treatment of Neurological Bladder, however, interdisciplinary treatment is also necessary to reduce symptoms and signs, in physical and emotional disorders, in improving social life and especially in improving the quality of life of these children.